2017
DOI: 10.1007/s00423-017-1568-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of post-thyroidectomy chronic asthenia: a prospective cohort study

Abstract: Purpose Chronic asthenia (CA) is complained by some patients that have undergone thyroid surgery. We evaluate its impact in patients undergoing unilateral or bilateral thyroidectomy, the trend during a 1-year follow-up, and the possible risk factors. Methods A prospective, cohort study was carried out on 263 patients scheduled for thyroidectomy from 2012 and 2014. Exclusion criteria were as follows: Graves' disease, malignancies requiring radioiodine therapy, post-surgical hypoparathyroidism, laryngeal nerve p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
10
3
Order By: Relevance
“…Although the majority of concurrent thyroid disease resulted was benign, a not negligible prevalence of incidentally discovered thyroid malignancy was previously reported. In particular, papillary microcarcinoma was disclosed in 12% of the series of 103 patients reported by Bentrem et al [12], 17.6% among the 51 patients reported by Kösem et al [19], 13% among the 85 patients reported by Latina et al [10], and 32.2% of the 231 patients belonging to a series by Scerrino et al [15].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although the majority of concurrent thyroid disease resulted was benign, a not negligible prevalence of incidentally discovered thyroid malignancy was previously reported. In particular, papillary microcarcinoma was disclosed in 12% of the series of 103 patients reported by Bentrem et al [12], 17.6% among the 51 patients reported by Kösem et al [19], 13% among the 85 patients reported by Latina et al [10], and 32.2% of the 231 patients belonging to a series by Scerrino et al [15].…”
Section: Discussionmentioning
confidence: 88%
“…Finally, the surgical approach to PHPT may be changed if thyroid disease is also present [9,15,16]. While the simultaneous TX and PTX are mandatory in case of malignancy suspicion, the surgical approach in case of concomitant thyroid disease unsuspected for malignancy is still debated [9,15,16]. Italian AME guidelines [17] in 2012 suggested to treat nodular thyroid disease concomitantly to PHPT, in order to avoid repetitive surgery that would be more worrisome owing to postsurgical adhesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term follow-up and information on mortality are not available, but the advanced stage of the PC at diagnosis likely predict a poor prognosis, worse than that of patients with classical hypercalcemic PC (2,7,9,(49)(50)(51)(52)(53). In the present case, we preferred to perform a thyroid lobectomy because of the pre-existent ipsi-lateral vocal fold paralysis and for taking the opportunity of avoiding the possible sequelae and complications of the total thyroidectomy (57)(58)(59)). An emostatic agent (gelatin-thrombin matrix) was used with the aim of preventing postoperative emorrhage (60,61).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 92%
“…These conclusions were confirmed in a 2011 BAETS consensus statement (53). In our opinion, a complete patient's information and the consequent informed consent is mandatory (54,55) for achieving the best results, especially in terms of patient's satisfaction.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%